Kartu Skor Poedji Rochyati in the Indonesian Maternal Referral System - Sihotang, Jojor; Hidayatullah, Amiruddin (Universitas Airlangga, 2024)
HIGHLIGHTS 1. This review focuses on maximizing the effectiveness of